Edukasi kandungan gizi dan sanitasi pada jajanan anak di SD Islam Ulun Nuha Medan - Koka, Ecia Meilonna; Tumanggor, Winni R.E.; Novia, Reni; Panjaitan, Arifa Masyitah; Zebua, Yunus Diel (TROPHICO, 2024)
Nutritional problems in children in Indonesia stem from what they eat, including the consumption of school snacks. Education on the nutritional content of school snacks must be provided to overcome the risk of snacks in school-age children to obtain balanced nutrition. The purpose of this study was to provide education on nutritional content and sanitation at SD Islam Ulun Nuha Medan. The design of this study used a pre-experiment with a one group pre-post-test design with a sample of 129 students from grade 5 to grade 6. Education was provided through lectures containing the concept of nutritional content and sanitation in children's snacks. Pre-test and post-test were conducted before and after the education using 10 question in questionnaire. The results of this activity show the pre-test and post-test that have been distributed before and after education, which shows that there is an increase in respondents' knowledge before and after being given education, which is 6.66 with a p-value of 0.0001. It’s shows that there is an influence of nutrition education on students' knowledge about nutritional and sanitation in snacks. The increase in knowledge can be caused by using lecture and demonstration methods with slide presentation media and examples of healthy and unhealthy snack foods. The use of the right methods and media greatly affects the results of education where the more senses are exposed, the easier it is to understand a message.